Perancangan Sistem Informasi Pengaduan dan Aspirasi Masyarakat Desa Berbasis Web dengan Metode Rapid Application Development (RAD) - Miftah Dwi Lestari; Junaidi Junaidi; Satriandi Satriandi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The development of information technology has encouraged improvements in public service quality, including at the village government level. In Sunggal Kanan Village, Sunggal District, Deli Serdang Regency, the process of submitting public complaints and aspirations is still carried out manually, resulting in issues related to documentation, transparency, and follow-up actions. This study aims to design and develop a web-based Village Public Complaint and Aspiration Information System using the Rapid Application Development (RAD) method. The RAD method was chosen because it emphasizes fast system development through iterative stages involving active user participation, namely Requirements Planning, User Design, Construction, and Cutover. Data collection techniques included observation, interviews, and literature studies. The developed system provides features such as user registration and login, complaint and aspiration submission forms, report status tracking, and an admin dashboard for managing and following up on reports. The results show that the system improves efficiency, transparency, and accountability in managing public aspirations. Through this system, citizens can submit reports online without visiting the village office and monitor their report status in real time. The implementation of the RAD method proved effective in delivering a system that meets user needs within a relatively short development time.